Laser Fabrication and Performance of Flexible Pressure Sensors with Ridge-Mimicking Spatially Ordered Microstructures - Linjing Wu; Chao Gao; Jincheng Wang; Chen Zhang; Yuzhi Ke (Micromachines)
The proliferation of flexible pressure sensors has generated new demands for high-sensitivity and low-cost sensors. Here, we propose an elegant strategy to address this challenge by taking a ridge-mimicking, gradient-varying, spatially ordered microstructure as the sensing layer, with laser processing and interdigitated electrodes as the upper and lower electrode layers. Simultaneously, the entire structure is encapsulated with polyimide (PI) tape for protection, and the fabrication process is relatively feasible, facilitating easy scaling. The presented results show that the flexible pressure sensor exhibits a sensitivity of 1.65 kPa−1 across a pressure range of 0 to 1100 kPa. Furthermore, the sensor displays low hysteresis, as well as rapid response and recovery times of 62 ms and 83 ms, respectively. Finally, we demonstrate the application potential of the sensor for monitoring joint movements, especially for detecting pressure and direction in finger joints. This technology shows great potential for applications in smart robotics, wearable devices, health monitoring, and other emerging technologies.